Large Free-Floating Right Atrial Thrombus - Sanhitha Valasareddy; Issac Rhea (Annals of Internal Medicine: Clinical Cases)
We present the images of a 67-year-old man who came to the emergency department with bilateral lower extremity pain and shortness of breath. Our images include an intraoperative transesophageal echocardiogram that shows a large, continuous free-floating right atrial mass and a large 31 cm × 1 cm thrombus that was successfully extracted. The thrombus likely could not embolize because of the patient's severe heart failure.